Empoderamento feminino e resiliência de artesãs por meio do saber-fazer manual têxtil: estudo de caso das bordadeiras de Barra Longa-MG - Bianca Xavier Lemes (2022)
This research addresses the know-how of the traditional craft of weaving, covering the material and symbolic dimension that are established around the craft, such as the techniques of the way of doing, tradition, memory, identity, belonging and the social relationships. In this sense, we sought to understand, through an interdisciplinary view, how that know-how acts as a cultural resource in the processes of empowerment and resilience of artisans in textile crafts. The case of the embroiderers of the city of Barra Longa, State of Minas Gerais, was observed, in face of a peculiar context of the contemporary scenario - the rupture of an ore tailings dam that brought immeasurable impacts to the affected communities. The study aimed to understand how local embroiderers have been rebuilding and giving new meaning to traumas, through the craft of embroidery. The various approaches to the concepts of empowerment and resilience and their applications in the cultural and social scope were investigated, contributing to female emancipation and to the improvement of the people' quality of life, through their culture and community ties. The research also pointed to new perspectives to expand the safeguard of embroidery as a Cultural Heritage of the city of Barra Longa, in a participatory process, in which the values of cultural references are recognized by the community itself, culminating in the proposal of the Intangible Registration Process and other actions of valorization and diffusion of the cultural reference. The investigation was based on qualitative research, choosing the case study of the embroiderers in the city of Barra Longa, through participatory research in which the researcher was able to intertwine experiences and approach the universe of knowledge of the artisans. The results indicated the importance of preserving and valuing the textile craft, since it positively collaborates with the processes of female empowerment and resilience of the subjects, favoring various social, cultural and economic aspects, such as the recognition of the holders of know-how, social cohesion, self-esteem, autonomy, the resignification of traumas and community awareness, in the formation of subjects as protagonists of their culture.